Analisis Kinerja Keuangan Dengan Metode Economic Value Added (Eva) Dan Financial Value Added (Fva): (Studi Kasus pada PT Semen Tonasa) - Gani, Tharisa; Sumatriani, Sumatriani; Iqbal, Muhammad (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2024)
The company's performance could be assessed through the profit it earned, but profit did not always reflect positive financial performance. This study was motivated by a decrease in profit experienced by one of the largest cement producers in Eastern Indonesia, which was PT Semen Tonasa. The purpose of this study was to measure the financial performance of PT Semen Tonasa from 2018 to 2022 using the Economic Value Added (EVA) and Financial Value Added (FVA) methods. This study used a descriptive quantitative approach. Data collection techniques involved document studies and interviews. The results showed that in 2018, the company recorded negative EVA and FVA values, indicating poor financial performance. This reflected that operational activities during that period were unable to create value for the company. In contrast, from 2019 to 2022, the company obtained positive EVA and FVA values, indicating good financial performance. This reflected that operational activities during this period were able to create value for the company.Keywords: Financial Performance, EVA, FVA